Association of Lifestyle Factors With Abdominal Subcutaneous and Visceral Adiposity: The Framingham Heart Study - Molenaar, Esther A. (American Diabetes Association, 2009)
OBJECTIVE— The purpose of this study was to assess the relationship between lifestyle factors and abdominal subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT) in a community-based setting. RESEARCH DESIGN AND METHODS— Cross-sectional associations between lifestyle factors (dietary quality, physical activity, smoking, and alcohol consumption) and SAT and VAT volumes were examined in 2,926 Framingham Heart Study participants (48.6% women, aged 50 ± 10 years). RESULTS— Diets consistent with the 2005 Dietary Guidelines Adherence Index and greater physical activity were inversely associated with SAT and VAT (P < 0.0001–0.002). In men, former smoking was associated with higher SAT (2,743 ± 56 cm(3)) compared with current smokers (2,629 ± 88 cm(3)) or those who never smoked (2,538 ± 44 cm(3); P = 0.02). Both former and current smoking was associated with higher VAT (P = 0.03 [women]; P = 0.005 [men]). Women with high amounts of alcohol intake (>7 drinks/week) had lower SAT (2,869 ± 106 cm(3)) than those who consumed less alcohol (3,184 ± 44 cm(3), P = 0.006); significant differences in VAT were not observed (P = 0.18). In men, high amounts of alcohol intake (>14 drinks/week) were associated with higher VAT (2,272 ± 59 cm(3)) compared with intake of ≤14 drinks/week (2,139 ± 25 cm(3), P = 0.04), whereas SAT did not differ (P = 0.91). An increasing number of healthy lifestyle factors were associated with lower SAT and VAT volumes (all P < 0.003). CONCLUSIONS— Adherence to recommended dietary guidelines and physical activity are associated with lower SAT and VAT volumes. However, both smoking and high alcohol intake are differentially associated with VAT volumes. Further research to uncover the putative mechanisms is warranted.